Implementation of an e-Learning course in physical activity and sedentary behavior for pre- and in-service early childhood educators: Evaluation of the TEACH pilot study - Bruijns, Brianne A.; Vanderloo, Leigh M.; Johnson, Andrew M.; Adamo, Kristi B.; Burke, Shauna M.; Carson, Valerie; Heydon, Rachel; Irwin, Jennifer D.; Naylor, Patti-Jean; Timmons, Brian W.; Tucker, Patricia (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Childcare-based physical activity (PA) and sedentary behavior (SB) interventions have traditionally used in-person training to supplement early childhood educators’ (ECEs) knowledge and confidence to facilitate physically active programming for the children in their care. However, this method of delivery is resource-intensive and unable to reach a high number of ECEs. The purpose of the Training pre-service EArly CHildhood educators in PA (TEACH) pilot study was to test the implementation (e.g., fidelity, feasibility, acceptability) of an e-Learning course targeting PA and SB among a sample of pre-service (i.e., post-secondary students) and in-service (i.e., practicing) ECEs in Canada. Methods A pre-/post-study design was adopted for this pilot study, and implementation outcomes were assessed cross-sectionally at post-intervention. Pre-service ECEs were purposefully recruited from three Canadian colleges and in-service ECEs were recruited via social media. Upon completing the e-Learning course, process evaluation surveys (n = 32 pre-service and 121 in-service ECEs) and interviews (n = 3 pre-service and 8 in-service ECEs) were completed to gather ECEs’ perspectives on the e-Learning course. Fidelity was measured via e-Learning course metrics retrieved from the web platform. Descriptive statistics were calculated for quantitative data, and thematic analysis was conducted to analyze qualitative data. Results Moderate-to-high fidelity to the TEACH study e-Learning course was exhibited by pre-service (68%) and in-service (63%) ECEs. Participants reported that the course was highly acceptable, compatible, effective, feasible, and appropriate in complexity; however, some ECEs experienced technical difficulties with the e-Learning platform and noted a longer than anticipated course duration. The most enjoyed content for pre- and in-service ECEs focused on outdoor play (87.5% and 91.7%, respectively) and risky play (84.4% and 88.4%, respectively). Conclusions These findings demonstrate the value of e-Learning for professional development interventions for ECEs. Participant feedback will be used to make improvements to the TEACH e-Learning course to improve scalability of this training.